2020
DOI: 10.1080/20905068.2020.1832648
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patient safety culture perception among healthcare workers in intensive care units of Alexandria Main University Hospital, Egypt

Abstract: Background: Patient safety culture (PSC) is a vital feature to assess the ability of any healthcare setting in addressing and reducing patients harm. This study attempted to assess the PSC in Intensive Care Units (ICUs) at Alexandria Main University Hospital (AMUH) from the point of view of physicians and nurses. Methods: A cross-sectional study was implemented in two ICUs at AMUH over period of six months. Seventy-two participants were interviewed using the Hospital Patient Safety Scale, customized by the Age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Only 40 (4.5%) included studies reported the use of incentives for participation, such as the distribution of ballots for gift certificates,35 raffles for various prizes33 or compensation checks after questionnaire completion 36. Staff time constraints was a common reason provided for low response 36 37. Poor timing was particularly identified as an issue during the COVID-19 pandemic, with increased hospital staff workloads and additional ethical constraints in data collection at this time 38–40…”
Section: Resultsmentioning
confidence: 99%
“…Only 40 (4.5%) included studies reported the use of incentives for participation, such as the distribution of ballots for gift certificates,35 raffles for various prizes33 or compensation checks after questionnaire completion 36. Staff time constraints was a common reason provided for low response 36 37. Poor timing was particularly identified as an issue during the COVID-19 pandemic, with increased hospital staff workloads and additional ethical constraints in data collection at this time 38–40…”
Section: Resultsmentioning
confidence: 99%
“…This negative attitude was highlighted in studies conducted in the study settings [ 49 51 ]. Poor prevailing patient safety culture is a another concern explaining missed perioperative nursing care since previous works in the study settings found poor perception of healthcare providers for patient safety culture [ 52 54 ]. Poor staff compliance with patient safety guidelines as well as lack of awareness about risk mitigation are also critical factors explaining the missed care items in our study.…”
Section: Discussionmentioning
confidence: 99%
“…37 Similarly, in a third study conducted among physicians and nurses in the intensive care units in Alexandria University Hospital in August 2018-January 2019, the dimension ''non-punitive response to errors" had the lowest scores, compared to other safety culture dimensions by respondents. 38 The minimal influence of fear on reporting behaviors could be explained by the anonymous and confidential nature of the Egyptian reporting system. Additionally, in this study, the reporting was limited to the clinical pharmacists, who are mostly not involved in the error.…”
Section: Discussionmentioning
confidence: 99%